Characteristics of Warm Acupuncture Reported in Experimental Studies: A Descriptive Narrative Review - Ji Won Choi; Seo Young Choi; Ji Sun Lee; Gi Young Yang (MEDrang Inc., 2019)
Background This study aimed to investigate the correlation between heat transmission and intervention factors for warm acupuncture (such as features of acupuncture material and moxa, the treatment method, and clinical symptoms). Methods Korean, English, Chinese and Japanese databases were analysed. Experimental studies that explored the association between thermal stimulation delivery and warm acupuncture intervention factors were included. The peak temperature, time to reach the peak temperature, and time of the effective stimulus, were set as the major parameters and analysed. Results A total of 12 studies were included. Two studies were associated with the acupuncture needle material, 4 studies associated with the moxa mass, 1 study associated with the moxa density, 2 studies associated with the location of ignition, and 1 study associated with treatment environment were reviewed. The reporting quality of the 12 studies was low. Conclusions This study provided limited information because of the heterogeneity of materials and parameters depending on each experiment. Further studies should clarify the correlation between heat transmission and intervention factors for warm acupuncture.